Challenges of Adoption of Automation for Library Operations in University of Calabar Library, Nigeria. - Patience Owere Ekpang; Dymphina Anyingang Abua (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
The influence of ICT has been felt in almost all aspects of daily life in today’s modern world. Information and communication technologies (ICTs) have brought tremendous changes in the process of transmission and management, particularly in the current library services. In fact, the automation of libraries is one of the major changes brought about by the development of ICTs. It has enabled us to transform the traditional system of libraries into a more modern set up. It improves the status of the library and reduces the work load of library professionals. It enables information dissemination efficiently from the enormous collection of information resources. The study investigated the challenges of the adoption of automation for library operations in the University of Calabar library, Nigeria. The study adopted descriptive survey research. A sample of 69 library staff, including professional and paraprofessional librarians, was selected for the study. The study adopted purposive and accidental non-probability sampling techniques. The questionnaire was used to collect data. Simple frequency tables were used to analyze the data. The findings of the study showed that there were insufficient funds, irregular power supply, inadequate funds for the project, inadequate ICT infrastructure, absence of staff training, lack of political will, poor maintenance culture, and a negative staff attitude towards automation projects. The study recommends the following: provision of a standby generator for adequate power supply; improved funding for automation projects; proper planning; and lastly, training and retraining of library staff in ICT skills.